2022
DOI: 10.7717/peerj.12846
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin S are involved in human carotid atherosclerotic disease progression, mainly by mediating phagosomes: bioinformatics and in vivo and vitro experiments

Abstract: Background Atherosclerosis emerges as a result of multiple dynamic cell processes including endothelial damage, inflammatory and immune cell infiltration, foam cell formation, plaque rupture, and thrombosis. Animal experiments have indicated that cathepsins (CTSs) mediate the antigen transmission and inflammatory response involved in the atherosclerosis process, but the specific signal pathways and target cells of the CTSs involved in atherosclerosis are unknown. Methods We used the GEO query package to down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Upregulated gene network analysis had 86 nodes and 91 edges with 2116 average number of neighbors and downregulated gene network analysis had 196 nodes, 452 edges and 4612 average number of neighbors. Gene network analysis of top 100 downregulated genes identified novel interactions among genes such as CD4 and Beclin1 as well as CTSS, which is known to be impaired in atherosclerosis 23 . H4C6, a histone coding gene interacted with STAG1, KIF20A and other histone protein coding genes such as H3-3B (Figure 4A).…”
Section: Resultsmentioning
confidence: 99%
“…Upregulated gene network analysis had 86 nodes and 91 edges with 2116 average number of neighbors and downregulated gene network analysis had 196 nodes, 452 edges and 4612 average number of neighbors. Gene network analysis of top 100 downregulated genes identified novel interactions among genes such as CD4 and Beclin1 as well as CTSS, which is known to be impaired in atherosclerosis 23 . H4C6, a histone coding gene interacted with STAG1, KIF20A and other histone protein coding genes such as H3-3B (Figure 4A).…”
Section: Resultsmentioning
confidence: 99%
“…CD163 is expressed only in monocytes and macrophages, and levels of the soluble form of CD163 (sCD163) are elevated in low-grade inflammation [ 26 ], which may be involved in chronic inflammatory responses and possibly in AMI and DN development through the induction of foam cell formation and local inflammatory responses. CTSS degrades damaged or unwanted proteins in lysosomes, regulates antigen presentation in atherosclerosis [ 27 ], and mediates phagosome involvement in atherosclerosis progression through macrophages [ 28 ]. CTSS is also a biomarker of chronic kidney disease, and as the glomerular filtration rate decreases, CTSS increases, exacerbating inflammation-associated endothelial dysfunction [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cathepsins (Cat) are a class of proteases responsible for antigen presentation, cell signaling and receptor activation, and Cathepsin S (CTSS) is a cysteine‐like protease that plays an important regulatory role 28–31 . Published animal experiments have shown that the number and percentage of macrophages and neutrophils in mice with Cat gene deficiency were lower than those in the wild‐type group, 32 suggesting that Cat may be involved in the formation of granulomatous structures. Cathepsin Z (CTSZ) participates in the host's immune defense through phagocytosis, signal transduction, proliferation and migration of immune cells such as monocytes, macrophages and dendritic cells 33,34 .…”
Section: Discussionmentioning
confidence: 99%